Human Capital Management in the Public Sectors within The Framework of the New Moroccan Development Model - Mekkaoui, Karim (The Arab Journal of Administration, 2024)
Since the 1990s, Morocco has embarked on a vast project of change and has responded to many transformations. These changes are primarily economic, social and environmental, and are characterized by the desire for more competitive integration into international trade. It is wise to remember in this regard that all developed countries seem to make a permanent commitment to the development of their human capital that was born in the course of these transformations. Human capital management also plays an important role in the competitiveness of sectors, especially in the performance of public services. Within this framework, Morocco is committed to translating its new development model, under the guidance of His Majesty King Mohammed VI, in all its institutions to be able to compete in various sectors. These efforts are considered a key player in developing the country’s economic and social competencies in light of the global changes. In this article, we will try to focus on explaining and analyzing Morocco’s experience in activating the new development model, which is a key actor that aims to establish a modern administration close to citizens and provide high-quality services. Taking into account the management of human capital in the public sectors at the core of the strategic importance of this model. To this end, it is important to focus on following the guidelines contained in the report of this model, as it gives priority to the human capital that exercises public sector services in order to enhance services of high quality and satisfaction for citizens, as well as focus. We will use the qualitative approach through a documentary analysis. We aim to explain, in this article, an inventory of the efforts and measures taken by the Moroccan government in the field of strengthening human capital management within the framework of the directions of the new development model, with a focus on the health and education sectors.